2010
DOI: 10.1177/0883073810369380
|View full text |Cite
|
Sign up to set email alerts
|

The Apnea Test: Rationale, Confounders, and Criticism

Abstract: The apnea test is recommended for the diagnosis of brain death. There are several reasons this test should be reconsidered. Confounding factors for performing the test are vaguely and poorly specified. The following 2 confounders are usually present and not considered: potentially reversible high cervical spinal cord injury and central endocrine failure of adrenal and thyroid axes. There are case reports of breathing at a higher partial pressure of arterial carbon dioxide threshold and cases of recovery of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 71 publications
0
49
0
1
Order By: Relevance
“…However, high cervical spinal cord injury and endocrine dysfunction can also invalidate the apnea test, and these confounds are not as often considered in the diagnosis, though they can be common in patients with suspected brain death. 34 Perhaps more concerning, hypercarbia (which is deliberately induced in the apnea test) is known to increase ICP and therefore can worsen ischemic injury to the brain, potentially contributing to herniation, and thus can be dangerous to a recently injured …”
Section: Controversies Surrounding the Tests And Pathophysiology Of Bmentioning
confidence: 99%
See 2 more Smart Citations
“…However, high cervical spinal cord injury and endocrine dysfunction can also invalidate the apnea test, and these confounds are not as often considered in the diagnosis, though they can be common in patients with suspected brain death. 34 Perhaps more concerning, hypercarbia (which is deliberately induced in the apnea test) is known to increase ICP and therefore can worsen ischemic injury to the brain, potentially contributing to herniation, and thus can be dangerous to a recently injured …”
Section: Controversies Surrounding the Tests And Pathophysiology Of Bmentioning
confidence: 99%
“…[34][35][36] "Indeed", Joffe et al wrote, "it is reasonable to suggest that the apnea test itself can result in failing the apnea test, creating a self-fulfilling prophecy". 34 Finally, although eupneic inspiratory efforts are stimulated by hypercarbia in the setting of normal physiology, in the context of the specific pathophysiology of a cascade of rostral-caudal dysfunction in which the lower medulla will be the final anatomic area to be compromised, the appropriate stimulus would be hypoxia (not hypercarbia), because hypoxia stimulates the lower medulla-mediated gasping reflex. 34 Some concerns regarding the safety of the apnea test have been discussed in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these criteria listed the adverse changes in the patient's general condition that indicate the need to disrupt the test: cardiac arrhythmia, hypotension with SBP ≤ 90 mm Hg, and significant desaturation (SpO2 < 85%) [7]. The need to perform AT has been questioned (in paediatric literature), and some authors have proposed to limit the test to only one probe [8,9].…”
mentioning
confidence: 99%
“…The apnea test has specifically been criticized for its nonspecificity, variability in its application, and lack of solid philosophical rationale. 6 In fact, some clinicians have abandoned the current apnea test guidelines. The authors of a recent retrospective chart review reported that in Canadian PICUs 18% of patients who were declared "brain dead" did not undergo an apnea test.…”
mentioning
confidence: 99%